The first 10 yards : the 5 dynamics of entrepreneurship and how they made a difference at DHL and other successful startups - Po, Chung (Gale virtual reference library, 2009)
Explores how to survive the "first ten yards" of a new company and thrive. Addresses the critical factors that determine the success or failure of any new business venture.